Paradoxomys cancrivorus Ameghino, 1885 (Rodentia, Hystricognathi, Erethizontidae): the first porcupine from the "Mesopotamian" (Late Miocene) (Ameghiniana, 2014)
Paradoxomys cancrivorus Ameghino is redescribed on the basis of a cast of the holotype, which is the only material currently available. The poorly preserved fossil and the fact that it was later lost, made the systematic history of P. cancrivorus quite complicated. The characters visible in the cast are: 1) brachydont molars. with very convex walls and with the mesoflexid extended across three quarters of the width of the occlusal surface, 2) medium size associated with this kind of molar and 3) sub-vertical symphysis. This allows us to refer it to the family Erethizontidae. Thus, it represents the first porcupine for the "Mesopotamian". The incisor and mandibular morphologies suggest that P. cancrivorus may be more closely related to the radiation of living porcupines than to the porcupines of the Late Oligocene-Middle Miocene Patagonian radiation. If the suggested affinities are correct, they reinforce the biogeographic relationships of the "Mesopotamian" fauna with that of northern South America.